When meniscal injury is not just a sports injury – a literature review of mechanisms, risk factors, and management in high-performance athletes - Bursztyn, Michał; Szaryński, Mikołaj; Sikorski, Adam; Kadłubowska, Karolina; Jakubowska, Paulina; Chojnowska, Natalia; Rytel, Jan; Jakubowska, Martyna; Gólcz, Adrian; Bursztyn, Tomasz; et al. (Quality in Sport, 2025)
<article class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="254e40d6-3991-4bb6-9725-287b9d039ed9" data-testid="conversation-turn-2" data-scroll-anchor="true" data-turn="assistant"> <div class="[–thread-content-max-width:40rem] thread-lg:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="90cabbd1-d386-495a-aa0a-d2e634f678c8" data-message-model-slug="gpt-5-1"> Menisci play a crucial biomechanical, stabilizing, sensory, and nutritional role in the knee joint, and their limited vascularization influences healing potential and treatment strategies. Meniscal tears are common, especially alongside anterior cruciate ligament (ACL) injuries, with characteristic tear types including bucket-handle, radial, flap, longitudinal, and horizontal lesions differing in frequency, treatment difficulty, and prognosis. Elite athletes are particularly vulnerable to meniscal injuries due to high mechanical loads, pivoting movements, contact mechanisms, and sport-specific demands; the risk further increases with concomitant ACL rupture and delayed reconstruction. Diagnosis requires a combination of clinical assessment and imaging, with MRI remaining the gold standard, and arthroscopy indicated in complex or uncertain cases. Treatment prioritizes meniscal preservation through repair whenever possible, as it offers better long-term joint protection despite longer rehabilitation compared to partial meniscectomy. Rehabilitation in elite athletes follows phased protocols emphasizing early protection, progressive loading, neuromuscular training, and functional testing to guide return-to-sport decisions. Preventive strategies focus on proprioceptive training and load management. Overall, optimal outcomes in athletes depend on accurate injury characterization, tissue-preserving treatment, and individualized rehabilitation aimed at restoring full function and minimizing long-term joint degeneration.